The curing of hides and skins in European prehistory - Groenman-van Waateringe, W.
Leather, hide and fur were probably the preferred material for all kinds of equipment (tents, bags, pots and drinking vessels) and clothing in prehistory. It is therefore remarkable that our knowledge of this material is so restricted, and its survival even in suitable circumstances very limited. Palynological data and experimental methods attempt to explain this phenomenon.